Contemporary Demographic, Treatment, and Geographic Distribution Patterns for Disorders of Sex Development. (March 2018) - Tejwani, Rohit; Jiang, Ruiyang; Wolf, Steven; Adkins, Deanna W.; Young, Brian J.; Alkazemi, Muhammad; Wiener, John S.; Pomann, Gina-Maria; Purves, J. Todd; Routh, Jonathan C.
This study aimed to describe the demographic characteristics, hospital utilizations, patterns of inpatient surgical management, and the overall state/regional variation in surgery rate among patients with disorders of sex development (DSD). We analyzed the Nationwide Inpatient Sample from 2001 to 2012 for patients younger than 21 years. DSD-related diagnoses and procedures were identified via International Classification of Diseases, Ninth Revision (ICD-9) codes. We identified a total of 43, 968 DSD-related admissions. Of these, 73.4% of the admissions were designated as female and 642 (1.9%) were inpatient surgical admissions. Among neonates, less than 1% underwent any type of genital surgery. Nonsurgical admissions were associated with longer length of stay and higher cost. There was no significant regional variation in the rate of DSD surgeries, but we observed higher concentrations of DSD surgeries in states associated with tertiary referral centers.